967. Inhibition of Host Neuraminidase Increases Susceptibility to Invasive Pulmonary Aspergillosis. (26th November 2018) - Van De Veerdonk, Frank; Dewi, Intan; Cunha, Christina; vanderBeeke, Lore; Jaeger, Martin; Gresnigt, Mark; Resendiz, Agustin; Lagrou, Katrien; Van De Velde, Greetje; Wauters, Joost; Carvalho, Agostinho
Abstract: Background: Influenza-associated aspergillosis (IAA) is an emerging fungal infection with high mortality and morbidity and the pathogenesis of this disease is not well understood. Interestingly, the number of IAA case reports has increased since the widespread use of neuraminidase inhibitors, such as oseltamivir in 2009. We set out to determine whether oseltamivir could contribute to the pathogenesis of IAA by modulating host responses. Methods: First, peripheral blood mononuclear cells (PBMCs) and neutrophils from healthy donors were stimulated with neuraminidase (NA)-treated A. fumigatus or were pre-exposed to NA prior to stimulation with Aspergillus conidia. In addition, PBMCs and neutrophils were pretreated with oseltamivir carboxylate prior to stimulation. Cytokines were measured from supernatants after 24 hours of incubation at 37°C. C57BL/6 and BALB/c mice were treated with oseltamivir prior to intranasal challenge with A. fumigatus . Immunosuppression was induced by corticosteroid or cyclophosphamide. Results: We demonstrate that Aspergillus treated with NA induced an enhanced immune response. Moreover, PBMCs and neutrophils treated with NA produced increased cytokine responses. Blocking NA in vitro with oseltamivir reduced Aspergillus -induced cytokine responses. Next we investigated the effects of blocking neuraminidase activity with oseltamivir in vivo. Immunocompetent mice and mice treated with corticosteroids showed increased mortality, lung fungal burden, and decreased cytokine production when treated with oseltamivir. These effects were not observed in cyclophosphamide-treated mice, suggesting that the effects of NA activity in anti- Aspergillus host defense acts mainly via myeloid cells. Conclusion: Our results provide evidence that host neuraminidase activity is important for protective anti- Aspergillus immune responses. Treatment with oseltamivir, thus blocking host NA activity, in a setting of corticosteroid use might therefore increase susceptibility to Aspergillus infection. These results warrant further study on the role of neuraminidase and the effects of oseltamivir on susceptibility to invasive pulmonary aspergillosis during active influenza infection. Disclosures: All authors: No reported disclosures.